Logistics value co-creation in sustainable last-mile delivery: Evidence from parcel lockers in Indonesia - Lesmini, Lis; Firdaus, Muhammad Iqbal; Agusinta, Lira; Yulihapsari, Ika Utami (Asian Management and Business Review, 2026)
Indonesia’s rapid e-commerce growth has intensified pressure on last-mile delivery (LMD) systems, making sustainable and consumer-centric solutions increasingly urgent. While self-collection parcel (SCP) lockers offer promising alternatives to conventional home delivery, their adoption remains limited despite mounting urban logistics inefficiencies. Drawing on service-dominant logic (SDL), this study examines how logistics value, utilitarian and hedonic orientations, and environmental knowledge influence consumers’ willingness to co-create and, subsequently, their intention to adopt SCPs. A quantitative cross-sectional survey was administered to 235 online shoppers in Greater Jakarta, selected through purposive sampling from a target population of active online marketplace users with prior e-commerce experience. Data were collected electronically via a structured questionnaire distributed through online channels and analyzed using partial least squares structural equation modeling (PLS-SEM). Results confirm that logistics value, utilitarian orientation, hedonic orientation, and environmental knowledge each positively influence willingness to co-create. Furthermore, willingness to co-create and environmental knowledge directly and significantly predict SCP adoption intention. These findings advance SDL theory by positioning consumers as active operant resources in sustainable logistics ecosystems, moving beyond traditional efficiency-based perspectives. The study also contributes empirical evidence from a developing urban market, broadening the applicability of co-creation frameworks in contexts where infrastructure limitations and environmental awareness remain uneven. Practical guidance is offered for designing co-creation-oriented SCP services aligned with consumer motivations and sustainability goals.